Rate of decay for solutions of viscoelastic evolution equations - Mohammad Kafini (Electronic Journal of Differential Equations, 2013)
In this article we consider a Cauchy problem of a nonlinear viscoelastic equation of order four. Under suitable conditions on the initial data and the relaxation function, we prove polynomial and logarithmic decay of solutions.